HEAT RESISTANCE OF PUR ADHESIVE JOINTS OF WOOD CONSTRUCTIONS - Sedliaĉik, Ján (Innovation in Woodworking Industry and Engineering design, 2012)
The significance of this work consists in pointing out the fact that adhesive joints may be at conditions of increased temperature the weak points of the wood glued structure. The aim of this work is to find out if there is a relationship of the strength of glued joints at increased temperature determined as shear and bending strength of glued joints. The work determines strength properties of beech (Fagus silvatica) and spruce (Picea abies) glued joints at thermal load at 20 °C, 50 °C, 80 °C and 110 °C. For gluing of wood samples, there were applied adhesives from two producers of one component polyurethane (1C PUR) adhesives Jowapur 686.60 and Kestopur 1030. Both types of PUR adhesive systems showed a softening of the joints and also decreasing in shear and bending strength.